Fluorination in enhancing photoactivated antibacterial activity of Ru(ii) complexes with photo-labile ligands. Issue 42 (3rd July 2020) - Sun, Weize; Boerhan, Rena; Tian, Na; Feng, Yang; Lu, Jian; Wang, Xuesong; Zhou, Qianxiong
Abstract : Fluorination in the dppz ligand efficiently enhanced the photoactivated antibacterial activity of Ru(ii ) complexes with photo-labile ligands against antibiotic-resistant bacteria both under normoxic and hypoxic conditions. Abstract : Fluorination in enhancing photoactivated antibacterial activity of Ru(ii ) complexes with photo-labile ligands was studied. Ru(ii ) polypyridine complexes containing a di-fluorinated dppz (dipyrido[3, 2- a :2′, 3′- c ]phenazine) or mono-trifluoromethylated dppz bidentate ligand and four pyridine monodentate ligands (complexes 3 and 4 ) were found to show potent photoactivated antibacterial activity against methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), and Escherichia coli ( E. coli ) in both normoxic and hypoxic conditions. The bactericidal effect of complexes 3 and 4 under hypoxic conditions may stem from the fluorine-containing Ru(ii ) aqua species after photo-induced pyridine dissociation, and DNA may be the potential antibacterial target. Photosensitized singlet oxygen may also account for their antibacterial activity under normoxic conditions. Moreover, negligible hemolysis rates as well as low dark- and photo-cytotoxicity toward human normal liver cells (L-O2) were also observed for both complexes. Our work may provide new insights into the development of novel and efficient Ru(ii ) complex based photoactivatable antibacterial agents against antibiotic-resistant bacteria.